Pelatihan Keamanan Jaringan WAN dengan Mikrotik untuk Meningkatkan Kompetensi Keahlian Siswa SMK - Tahir, Muhlis; Purnamasari, Dian Neipa; Nazarullail, Fikri; Muamar, Muamar; Ardiansyah, Muhammad Risky; Putri, Aureliia Maharani; Firmansyah, Ifan Fauzi (Jurnal Pengabdian UNDIKMA, 2025)
This community service aims to enhance students’ skills in managing and securing school networks, with a focus on Mikrotik security configuration. The target participants were teachers and students of Computer and Network Engineering at SMKS-Al Muhajirin Arosbaya. The training methods included workshops, hands-on practice, and project-based evaluations to assess students’ understanding and skills. The results of the service showed a significant improvement in students’ ability to manage firewalls, VPN configurations, and bandwidth settings on Mikrotik. In addition, students are also able to identify and deal with cyber threats more effectively. These results showed that the training provided was not only relevant to the needs of the industry, but also helped students be better prepared to face challenges in the world of work. This service activity is important in preparing vocational school students as competent experts in the field of network security.